Calculus with Applications (10th Edition)

Published by Pearson
ISBN 10: 0321749006
ISBN 13: 978-0-32174-900-0

Chapter 2 - Nonlinear Functions - 2.2 Quadratic Functions; Translation and Reflection - 2.2 Exercises - Page 64: 11


$(2, -1)$

Work Step by Step

$ f(x)=a(x-h)^{2}+k^{2},\qquad$ vertex: (h,k) (solved as in example 4) $(A\pm B)^{2}=A^{2}\pm 2AB+B^{2}$ ----------- $y=-2x^{2}+8x-9$ $=-2(x^{2}-4x)-9$ $=-2(x^{2}-2\cdot 2\cdot x+4-4)-9$ $=-2(x^{2}-4x+4)-9-(-2)(4)$ $=-2(x-2)^{2}-1$ Vertex: $(2, -1)$.
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.